The costly prestige ranking of scholarly journals - Smedsrød, Bård; Longva, Leif (Ravnetrykk, 2020)
The prestige ranking of scholarly journals is costly to science and to society. Researchers’ payoff in terms of career progress is determined largely from where they publish their findings, and less from the content of their scholarly work. This fact creates perverted incentives for the researchers. Valuable research time is spent in trying to satisfy reviewers and editors, rather than spending their time in the most productive direction. This in turn leads to unnecessary long time from research findings are made until they become public. This costly system is upheld by the scholarly community itself. Scholars supply the journals with time, serving as reviewers and editors without any paycheck asked, even though the bulk of scientific journals are published by big commercial enterprises enjoying super profit margins. The super profit results from expensive licensing deals with the scholarly institutions. The free labour offered, on top of the payment for the licensing deals, should be viewed as part of the payment to these publishers – a payment in kind. Why not use this as a negotiating chip towards the publishers? If a publisher asks more than acceptable for a licensing deal, rather than walk away with no deal, the scholarly institutions could pull out all the free labour offered by reviewers and editors.